Quartz fabrics pattern along the Forcarei synform (NW Iberian Massif) and their tentative tectonic model - Fernández, F. J.; Díaz-García, F.; Marquínez, J. (TRABAJOS DE GEOLOGÍA, 2009)
Quartz fabric patterns investigated within a suite of metaquartzites collected from the Forcarei synform, in the most internal zone of the NW Iberian Massif, are used to interpret the detailed processes involved in fabric and fold evolution. Quartz fabrics related to the Variscan tectonic foliation S2 were formed by non-coaxial deformation and under 3-D general monoclinic flow. Regional stretching lineation is sub-horizontal and parallel to the general trend belt. Sinistral shear sense is indicated in both limbs of the synform using several indicators. Latter, coaxial horizontal shortening perpendicular to the L2 occurred during the third phase of the Variscan deformation and produced the tilting and uprighting of this large-scale fold. A laterally constricted shear zone system formed between the orthogonal flow directions of the upper and lower crust during the thinning of the orogenic wedge is tentatively proposed to explain the main Variscan D2 deformation event of the basal units and lower allochthon of the Galicia-Trás-os-Montes Zone.